P139 A randomised comparative study of cough peak expiratory flow (cpef) using full face mask vs mouthpiece interfaces in healthy subjects. (15th November 2017) - Mearns, A; Subhan, F; Roberts, L
Abstract : Background: Cough Peak Expiratory Flow (CPEF) is a respiratory muscle function test designed to assess the ability to clear airway secretions adequately. Present practice requires CPEF to be measured using a mouthpiece, which has proven problematic in patients the neuromuscular disease(s). The study aimed to determine the effectiveness of using a facemask vs mouthpiece in measuring CPEF. Hypothesis: CPEF measured via an Interurgical Anaesthetic Full-Face Mask will provide comparably similar (CI 0.95) Results to those obtained using a flanged mouthpiece. Participant Population: Healthy participants were recruited into the study through faculty newsletters, social media advertisements and random convenient sampling of network connexions. Participants were screened, following ethical approval, using a specifically-designed Pre-screening Medical Questionnaire (PSMQ) against an Inclusion criterion, before inclusion to the study. Methods: Testing procedure ensured standard spirometry position was adopted. The participant was asked to expire to residual volume (RV), followed by a rapid inhalation to total lung capacity (TLC) where a forceful cough manoeuvre was made. Procedure was repeated at least 3 times, with 45 s rest between attempts. A maximum of 8 attempts per interface was allowed, with a 10 min change-over period between interfaces. A students 2-sample t-test, Bland-Altman and regression analysis were employed to statistically analyse the data. Randomisation occurred using the exce RAND command on the sample ID's. Results: 60 healthy subjects were recruited, of which 58 participant's Results were deemed appropriate to study. The mean result of each interface was analysed to indicate no significant differences of CPEF measurements in healthy subjects (CI 95%, p=0.971). There were no significant differences between Age and Gender (CI 95%, Age p=0.453, Gender p=0.902) with the different interfaces. Analysis of each interfaces' maximal effort (CPEFmax ) indicated no significant differences (CI 95%, p=0.943). Randomised sequence data was analysed, where it concluded that there was no significant influence of interface sequencing on the Results (CI=95%, p=0.671). Conclusion: The study's Results support the hypothesis, suggesting interchangeability of both interfaces. This now offers a platform for further study in the viability of facemask CPEF within the clinical setting, as well as providing a standardised protocol and CPEF reference values.